Analisis Dampak Pandemi COVID 19 Terhadap Pemasaran Online di Kecil dan Usaha Menengah (UMKM) - Rahmi Hajriyanti; Rizaldi Akbar (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
This study aims to analyze the impact of the COVID 19 pandemic on online marketing for Micro, Small, and Medium Enterprises (MSMEs). The research method used in this research is descriptive analysis and is included in the type of library research. The output of this research is national and international journals. This research is expected to increase the growth of MSMEs through online marketing. The results of a literature review concluded that the coronavirus pandemic has had a significant impact on business actors around the world, including in Indonesia. Most business actors are forced to stop their business activities, because of policies issued by the government. This situation has an impact on reducing turnover. But on the other hand, there is a significant increase in online sales transactions so that it can become an opportunity for the growth of MSMEs by optimizing online marketing.